Formation mechanism of magnetic–plasmonic Ag@FeCo@Ag core–shell–shell nanoparticles: fact is more interesting than fiction1. Issue 36 (28th September 2015) - Takahashi, Mari; Higashimine, Koichi; Mohan, Priyank; Mott, Derrick M.; Maenosono, Shinya
<x xml:space="preserve">Abstract</x> The formation mechanism of Ag@FeCo@Ag core–shell–shell nanoparticles which are synthesized by the combination of a multi-step hot injection method and a polyol method was investigated by comparing several different derivative NPs such as Ag@FeCo, Ag@Co, Ag@Fe and FeCo NPs.